2016
DOI: 10.1063/1.4940436
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical error bounds for continuum discretisation via Gauss quadrature rules—A Lieb-Robinson bound approach

Abstract: Instances of discrete quantum systems coupled to a continuum of oscillators are ubiquitous in physics. Often the continua are approximated by a discreate set of modes. We derive error bounds on expectation values of system observables that have been time evolved under such discretised Hamiltonians. These bounds take on the form of a function of time and the number of discrete modes, where the discrete modes are chosen according to Gauss quadrature rules. The derivation makes use of tools from the field of Lieb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…We note that a complementary analysis of quantum Otto cycles in the strong coupling regime, also employing the RC mapping, appears in a related work by Newman et al [39]. Apart from the thermodynamic applications we propose here, it has been shown that such a RC mapping and related concepts can provide a very accurate method to investigate the behaviour of open quantum systems for a variety of problems [40][41][42][43][44][45][46][47][48][49][50][51]. Even more generally, it is possible to apply this method iteratively by including several RCs and in this way one can prove that every non-Markovian environment can be mapped to a Markovian one [52][53][54].Apart from adapting this general method to treat heat engines in the strong coupling and non-Markovian regime, we also consider concrete applications.…”
mentioning
confidence: 79%
“…We note that a complementary analysis of quantum Otto cycles in the strong coupling regime, also employing the RC mapping, appears in a related work by Newman et al [39]. Apart from the thermodynamic applications we propose here, it has been shown that such a RC mapping and related concepts can provide a very accurate method to investigate the behaviour of open quantum systems for a variety of problems [40][41][42][43][44][45][46][47][48][49][50][51]. Even more generally, it is possible to apply this method iteratively by including several RCs and in this way one can prove that every non-Markovian environment can be mapped to a Markovian one [52][53][54].Apart from adapting this general method to treat heat engines in the strong coupling and non-Markovian regime, we also consider concrete applications.…”
mentioning
confidence: 79%
“…Here, the difference to the phonon mapping is that Γ (n) (ω) are not analytically continued to the complete real axis, as ω > 0 is assumed throughout. The convergence properties of related recursion relations have been discussed in great detail [32,38,39].…”
Section: Particle Mappingmentioning
confidence: 99%
“…In the context of linear bosonic reservoirs (Caldeira-Leggett or Brownian motion models), this technique has a longer tradition 6 . It has found various applications in the theory of open quantum systems [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and it is also closely related to the "time evolving density matrix using orthogonal polynomials algorithm" (TEDOPA) [23][24][25][26][27][28] . We remark that, although it shares many similarities with the bosonic case, the RC mapping was not studied for fermionic reservoirs before.…”
Section: Introductionmentioning
confidence: 99%